Faktor Risiko Keterlambatan Diagnosis Kanker Pada Pasien Kanker Payudara: Systematic Literature Review - Kaljafa, Fertika Nanda; Puspikawati, Septa Indra; Aini, Putri Nur; Al Gifari, Tubagus Akhmad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: Delayed diagnosis of breast cancer is one of the behaviours commonly experienced by the public due to several risk factors that influence it. Objective: This study aims to identify risk factors that influence the delay in diagnosis of cancer in patients with breast cancer. Objective: This study aims to identify risk factors that influence the delay in diagnosis of cancer in patients with breast cancer. This type of research is a literature review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) model. Articles were obtained from online databases, namely Google Scholar and Neliti with a range of years 2020-2024. The results of the literature review found that the risk factors that affect the delay in diagnosis of cancer in breast patients include the level of education and knowledge, geographical location of the area in access to health services, information exposure, SADARI behaviour, husband support, feelings of fear and anxiety, misdiagnosis, age with a range of examinations at health services. As for some other risk factors that are not associated include family history of cancer, economic factors, initial complaints and alternative treatments. Education level and knowledge as well as SADARI behaviour are the factors that appear the most as risk factors that affect the delay in cancer diagnosis in breast cancer patients.